PERHITUNGAN BIAYA PROMOSI PADA UMKM DI DESA KUNYIT KABUPATEN TANAH LAUT - Bandi, Maulida Hirdianti; Mufrida; Amelia, Noor (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Tanah Laut (Politala), 2021)
The existence of UMKM cannot be eliminated from this nation's society because their existence is very beneficial in terms of distributing people's income. In carrying out its activities, marketing or promotional activities in a company have an important role, such as efforts to achieve the expected product sales targets. UMKM in Kunyit Village, Tanah Laut Regency as partners who collaborate in Community Service activities related to calculating promotional costs using the counseling method. During the implementation, there was a presentation of material regarding calculating promotional costs and continued with discussions and questions and answers with service participants. It is hoped that the results of this service will provide insight and improve the quality of human resources, especially regarding the calculation of promotional costs for UMKM in Kunyit Village.